2022
DOI: 10.51629/ijeamal.v3i2.93
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Job Satisfaction in Instructional Delivery Modalities, and the Role of School Leaders: A Study among Selected Private Schools in the UAE

Abstract: The purpose of this paper is twofold. Firstly, to analyse the impact of the newly applied instructional delivery modalities on teachers’ job satisfaction. Secondly, to navigate the role of school leaders to help teachers to cope with these models. The teaching modalities that are of research interest are the face-to-face, online, and hybrid models. The study adopted the mixed-methods approach. Around 151 teachers from 3 private schools in Abu Dhabi shared their response in a quantitative survey. To compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Furthermore, the results of hypothesis testing for stress coping and learning motivation indicated a significant positive correlation. The significance value of 0.001 and correlation coefficient of 0.318 suggested that effective stress coping strategies enhanced learning motivation among working college students (Yahya, 2022). This finding aligns with the statement by González-López (2021) that stress coping influences individual development by effectively dealing with stressful situations (van Katwijk et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the results of hypothesis testing for stress coping and learning motivation indicated a significant positive correlation. The significance value of 0.001 and correlation coefficient of 0.318 suggested that effective stress coping strategies enhanced learning motivation among working college students (Yahya, 2022). This finding aligns with the statement by González-López (2021) that stress coping influences individual development by effectively dealing with stressful situations (van Katwijk et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Understanding the relationship between leadership styles and teacher satisfaction is crucial for educational administrators aiming to create positive work environments and improve overall educational quality [34]- [36]. Teachers' job satisfaction is influenced by various factors including interactions with department leadership, recognition of achievements, professional growth opportunities, student interaction, effective instruction, extracurricular involvement, and paid time off [37]. Teaching satisfaction has been found to be a critical protective factor for teachers, as it is associated with decreased levels of depression and anxiety and increased levels of life satisfaction [38].…”
Section: Teacher Satisfaction In Educational Contextsmentioning
confidence: 99%
“…Some factors might often be the cause of plagiarism behavior. Students may lack knowledge about writing scientific papers and plagiarism problems [10] [11], [12]. Laziness and desire to find shortcuts to achieve high achievements in desperate times may also lead to plagiarism.…”
Section: Introductionmentioning
confidence: 99%